The influence of transportation, social norms, cultural identity, and affective disposition in transnational media enjoyment - Wang, Jing; Ye, Qiqi; Shuai, Zhiqiang; Wang, Peifeng; Wang, Yujie; Lin, Changqing (Frontiers in Psychology, 2024)
The globalization of the media market is forcing decision-makers to understand the psychological processes behind local audiences' enjoyment of foreign TV dramas. However, there is a lack of research explicitly examining the act of viewing itself, particularly the pleasure audiences derive from interacting with media content. This study addresses this gap by integrating transportation theory and its expanded version. It aims to validate the influence of social norms, cultural identity, and affective disposition on narrative immersion while watching foreign TV dramas, as well as the subsequent enjoyment of media among local audiences. Seven hypotheses were tested in the study.The research employs a quantitative design, with responses collected from 353 students enrolled at a Malaysian public university. The findings demonstrate that the proposed model fits well with the data, supporting the seven hypotheses. Additionally, the results indicate that social norms, cultural identity, and affective disposition significantly influence transportation and enjoyment. Furthermore, the influence of cultural identity on social norms has a positive moderating effect on transportation.